FORMULATING CRITERIA FOR THE CIVIL RELATIONSHIP OF CHILDREN BORN OUT OF WEDLOCK AFTER CONSTITUTIONAL COURT DECISION NUMBER 46/PUU-VIII/2010 FROM THE PERSPECTIVE OF MASLAHAH ACCORDING TO ‘IZZ AL-DĪN IBN ‘ABD AL-SALĀM - Mahbub Ainur Rofiq; Mufidah Ch; Fakhruddin Fakhruddin; Musataklima Musataklima (JURNAL HAKAM, 2026)
This article examines the formulation of criteria for the civil relationship of children born out of wedlock after Constitutional Court Decision Number 46/PUU-VIII/2010 from the perspective of legal certainty and the maslahah theory of Izzuddin ibn Abdissalam. The study is grounded in the ambiguity of the phrase “children born outside marriage” and the clause “civil relationship” in the Constitutional Court decision, which has led to diverse interpretations and disparities in judicial decisions. This research is a normative juridical study employing statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources, including statutory regulations, Constitutional Court decisions, court decisions, Islamic legal doctrines, and relevant legal literature. The findings show that children born out of wedlock should not be treated as a single legal category. They need to be classified into three categories: children born from religiously valid but unregistered marriages, children born from defective marriages or relationships involving legal doubt, and children born from relationships without any marital bond. Each category produces different legal consequences, ranging from full, proportional, to limited civil relationships. This formulation aims to realize legal certainty, justice, utility, and maslahah while protecting children without undermining the legal order of lineage in Islamic family law.